Analisis Strategi Digital Marketing pada Usaha Pakaian melalui Platform TikTok Shop di Kota Jambi berdasarkan Etika Bisnis Islam - Nurul Fadhila Marza; Putri Apria Ningsih (Lembaga Yasin AlSys, 2026)
Studies on the application of Islamic business ethics in digital marketing practices continue to develop; however, research that specifically examines its implementation in clothing businesses using the TikTok Shop platform at the local level remains relatively limited. This study aimed to analyze the concepts of Islamic business ethics applied in digital marketing strategies of clothing businesses on TikTok Shop in Jambi City and to identify the constraints faced by business owners in their implementation. This research employed a qualitative approach with a case study design, involving clothing store owners on TikTok Shop selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed using thematic analysis through the stages of data reduction, data display, and conclusion drawing. The findings show that business owners have implemented Islamic business ethics through values of honesty, politeness, friendliness, and responsibility in their digital marketing activities. The dominant digital marketing strategies used include social media marketing, affiliate marketing, and the use of influencers, which were considered effective in increasing sales and brand awareness. However, constraints were still found in the form of limited understanding of Islamic business ethics principles among business owners and the less effective service provided when there was a surge in consumer demand. These findings provide a conceptual contribution to the development of studies on Islamic business ethics in the context of social commerce and offer practical implications for business owners to integrate syariah values more consistently into their digital marketing strategies, while also opening opportunities for further research with broader geographical coverage and more diverse methodological approaches.